Development Of An E-Module Assisted With Canva Oriented Higher Order Thinking Skills (HOTS) Momentum And Impulse Material - M. Paden, Thereziana; Widyaningsih, Sri Wahyu; Br. Sebayang, Sri Rosepda (Al-Khazini: Jurnal Pendidikan Fisika, 2025)
This research aims to develop an e-module assisted by Canva HOTS-oriented material on momentum and impulse into a valid, practical and effective e-module. Based on validation results by 3 HOTS-based e-module experts, the momentum and impulse material developed with the help of Canva is very valid with a validity level of . Based on the researcher's research on student responses when the e-module has been implemented, the practicality questionnaire data is at an interval of 87.88% so that the criteria for the practicality of the e-module are very practical. From the e-module effectiveness test based on questionnaire data, effectiveness is at an achievement level of 81.18%, so that the e-module effectiveness qualification based on the questionnaire is good or effective, and based on analysis of student completion data, the percentage of student completion is 94%, so that the e-module can said to be effective. From the results of the overall analysis of the data that the researchers obtained, it can be concluded that the HOTS-based e-module on momentum and impulse material developed with the help of Canva is very valid, very practical and effective.